Road Problem Diagnosis with Multi-Agent Systems in Traffic - Demir, Mert (Intelligent Methods In Engineering Sciences, 2023)
Today, traffic problems are important factors that cause loss of life and property. The fact that the drivers are not instantly unaware of the changing road and traffic conditions prevents taking early measures and triggers traffic problems. As an alternative to the deficiencies in the existing traffic cameras and observation systems, the model has been developed with each vehicle on the road as a unit of measurement. In the study, it is aimed to evaluate and share the road and traffic conditions between vehicles with a low-budget vehicle network module and to take early measures against possible problems. In this study, an early accident prevention method is presented by using multi-factor structures to monitor vehicle flow in traffic, detect road problems and take early precautions. The road hazard detection model was developed by making the prototype of the proposed system, and the model developed for the studies, experiments and early warning system to prevent possible traffic accidents was recommended for the prevention of traffic accidents in the future.